Keandalan Sistem Distribusi 20KV Pada Penyulang Sistem Distribusi PT.PLN UP3 Surabaya Utara Dengan Metode Reliability Network Equivalent Approach (RNEA) - Ma’rifanto Nur Ramadhan; Titiek Suheta; Novian Patria Uman Putra; Riny Sulistyowati; Nasyith Hananur Rohiem; Ilmiatul Masfufiah (Prosiding Seminar Nasional Sains dan Teknologi Terapan, 2022)
In an electrical energy service network, the quality of reliability can be known from the frequency of blackouts and the duration of blackouts in a certain time interval. Therefore, this study aims to determine the reliability of the 20 kV distribution network power system at the Distribution System Feeder PT.PLN UP3 North Surabaya and make efforts to increase the reliability index. The method chosen in conducting this research to determine the reliability index is the Reliability Network Equivalent Approach (RNEA) method. It is used to analyze the reliability of large and complex distribution systems with an equivalent element approach. Equivalent circuits are used to replace parts of the distribution network and rearrange the distribution system into a simple series. Based on the analysis obtained from the feeder, the SAIFI reliability index value is 1,303 times/customer/year and the SAIDI reliability index value is 3,303 hours/customer/year